Study on the structural influence mechanism of robot construction on real estate project costs: Moderating effect of management change - WEI, Xiujuan (Institutional Knowledge at Singapore Management University, 2024)
Cost control in construction is crucial for the survival of real estate enterprises. Especially in the context of cyclical downturns in the real estate industry, it is essential to achieve cost reduction and efficiency improvement in real estate projects. Currently, the widespread application of robotics technology may hold the key to achieving this goal. Robotics technology is widely recognized for its ability to automate tasks and reduce labor costs. However, it also brings about transformative impacts on management, organization, production, and processes, which can paradoxically increase project costs. Unfortunately, there is a lack of research focusing on the impact of robot construction—a new production model— on real estate project costs. Therefore, it is worth considering the following questions. How does robot construction specifically affect real estate project costs? What are the structural characteristics of the impact? What is the role of management change in this process? To address the aforementioned questions, leveraging my human capital strength, this study conducted a questionnaire survey focusing on real estate projects using robot construction within Group B I work for. A total of 162 respondent samples were collected from Group B across 31 cities in 13 provinces, including Guangdong in China. Additionally, the survey included 100 other real estate projects both domestically and internationally, such as the China Resources Center. Based on the internal questionnaire survey data from Group B, statistical analysis revealed that robot construction projects, on average, can reduce unit area costs by approximately 5%. Notably, labor costs showed a significant decrease, with the construction team size decreasing by around 20% on average, resulting in a reduction of approximately 10% in construction personnel costs. Furthermore, a scale system for robot construction was established to empirically analyze its impact on the cost of real estate projects. The study found that robot construction significantly suppresses average costs and redundancy costs. The mechanism test revealed that robot construction can leverage technological advantages like shortened production cycles and demonstrate superior adaptability in flexible resource allocation. The tension of technological advantages and the enhancement of adaptability can suppress the average costs and redundancy costs of real estate projects. Additionally, technological advantages and adaptability can mediate the relationship between robot construction and the cost of real estate projects. The heterogeneity analysis revealed that the cost-reducing effect of robot construction on real estate projects is more pronounced in scenarios with higher local wage levels and larger construction scales for the project. According to the moderating effect test, management change is a key mechanism by which robot construction suppresses the cost of real estate projects. It is within the context of organizational consensus cohesion, reinforced organizational learning, and human-robot collaborative operations that the expected efficiency of robot construction in reducing the cost of real estate projects can be fully realized and even strengthened. Finally, the extended test demonstrated that while robot construction reduces costs,it also optimizes organizational performance, thereby achieving the dual benefits of cost reduction and efficiency improvement. Based on the analysis of the external questionnaire survey, it was found that the willingness of real estate enterprises to adopt robot construction is generally weak. This phenomenon is closely related to factors such as competitive pressures, government support, organizational consensus, technological advantages, resource readiness, perceived usefulness, and perceived ease of use. According to the PSM survey on respondents’willingness to pay (WTP), the willingness cost for real estate projects constructed with robots varies from RMB 1,970.49 to 2,074.84, surpassing Group B’s cost of robot construction projects. Therefore, there is significant potential for the application and promotion of robot construction projects, and possibilities for collaboration between Group B and external enterprises can be further explored. The study’s findings offer a consistent and scientifically quantified evaluation of robot construction adoption in the real estate industry. They provide precise reference guidelines for advancing intelligent real estate construction, upgrading practices, and addressing cyclic downturns. Additionally, the conclusions present empirical support for the adoption and utilization of specialized construction robots, akin to those employed by Group B.